Store-Operated Calcium Channels Are Involved in Spontaneous Slow Calcium Oscillations in Striatal Neurons - Kikuta, Satomi; Iguchi, Yoshio; Kakizaki, Toshikazu; Kobayashi, Kazuto; Yanagawa, Yuchio; Takada, Masahiko; Osanai, Makoto (Frontiers in Cellular Neuroscience, 2019)
The striatum plays an important role in linking cortical activity to basal ganglia output. Striatal neurons exhibit spontaneous slow Ca2+ oscillations that result from Ca2+ release from the endoplasmic reticulum (ER) induced by the mGluR5-IP3R signaling cascade. The maximum duration of a single oscillatory event is about 300 s. A major question arises as to how such a long-duration Ca2+ elevation is maintained. Store-operated calcium channels (SOCCs) are one of the calcium (Ca2+)-permeable ion channels. SOCCs are opened by activating the metabotropic glutamate receptor type 5 and inositol 1,4,5-trisphosphate receptor (mGluR5-IP3R) signal transduction cascade and are related to the pathophysiology of several neurological disorders. However, the functions of SOCCs in striatal neurons remain unclear. Here, we show that SOCCs exert a functional role in striatal GABAergic neurons. Depletion of calcium stores from the ER induced large, sustained calcium entry that was blocked by SKF96365, an inhibitor of SOCCs. Moreover, the application of SKF96365 greatly reduced the frequency of slow Ca2+ oscillations. The present results indicate that SOCCs contribute to Ca2+ signaling in striatal GABAergic neurons, including medium spiny projection neurons (MSNs) and GABAergic interneurons, through elevated Ca2+ due to spontaneous slow Ca2+ oscillations.